The role of internal audit in risk management: a case study in UniSHAMS from employee perspectives - Mohd Isa, Nurul Hanisah (2025)
This study explores the role of Internal Audit Functions (IAF) in supporting risk management at Sultan Abdul Halim Mu’adzam Shah International Islamic University (UniSHAMS). Internal audits are vital for promoting good governance, ensuring transparency, and improving operational efficiency, especially in the context of higher education institutions. However, internal auditors often face challenges such as limited resources, lack of support, and insufficient training, which can hinder their ability to carry out their responsibilities effectively. The research adopts a qualitative approach, combining open-ended interviews and document analysis to better understand the gaps in internal audit practices. The study involves three internal auditors, each with over a decade of experience at UniSHAMS. The key patterns and underlying issues were identified through thematic analysis, providing a detailed view of how internal audit processes function at the university. The findings highlight how the effectiveness, challenges, and implementation of internal audit processes directly impact its role in UniSHAMS. These factors not only foster greater accountability and compliance but also contribute to enhancing overall institutional performance. This research offers valuable insights for researchers, university management, and the wider community on improving internal audit practices and addressing systemic issues more effectively.